OVERVIEW OF SUBMARINE MUD VOLCANO - Dung, Tran Tuan; Thanh, Phi Truong; Hung, Doan The (Vietnam Journal of Marine Science and Technology, 2014)
Mud volcanoes occur mostly within the sedimentary basins, both on land and seabed, where are weak areas of Earth crust or intersection of the fault systems. The activities of submarine mud volcano might cause potential risks for drilling operations and setting oil and gas pipeline on the sea floor. The activities of exploration and exploitation of oil and gas in the East Sea are pretty strong, especially in the sedimentary basins of the  continental shelf. Therefore, in this paper, the authors focus on essential analysis of some characteristics of mud volcanoes as well as the mechanism of formation and their relationships with gas hydrate, submarine landslide as a premise for the next researches.